Safety and Efficacy of Transcatheter Arterial Chemoembolization Plus Radiotherapy Combined With Sorafenib in Hepatocellular Carcinoma Showing Macrovascular Invasion - Zhao, Yuting; Zhu, Xianggao; Wang, Hongzhi; Dong, Dezuo; Gao, Song; Zhu, Xu; Wang, Weihu (Frontiers in Oncology, 2019)
The safety and efficacy of transcatheter arterial chemoembolization (TACE) plus intensity-modulated radiotherapy (IMRT) combined with sorafenib in hepatocellular carcinoma (HCC) showing macrovascular invasion (MVI) remain controversial. The records of 63 patients with HCC showing MVI, who underwent IMRT plus TACE combined with (28 participants; Group A) or without (35 participants; Group B) sorafenib from 2015 to 2018, were retrospectively reviewed to assess the progression-free survival (PFS), overall survival (OS), and treatment-associated toxicity. The median PFS was longer in Group A (13.6 months) than in Group B (9.2 months), and still significant after propensity score matching (PSM). However, the median OS was similar in the two groups (19.0 vs 15.2 months, P = 0.094 before PSM; P = 0.204 after PSM). The grade 3 hematologic and hepatic toxicity was present in 10 (15.9%) and 7 (11.1%) patients, respectively. The incidence of skin reaction, hand-foot syndrome, and diarrhea, all grade 1–2 adverse events, was significantly higher in Group A than in Group B. No patient experienced grade 4 or 5 toxicity, and radiation-induced liver disease was also not observed. TACE plus IMRT combined with sorafenib showed a good safety profile and clinical benefit in patients with HCC having MVI.